Reordenamientos moleculares en derivados de longipineno funcionalizados en los metilos geminales - Ruiz Ferrer, Cecilia (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
The partial or total hydrolysis of (3R,4S,5S,6S,9R,10R,11R)-9,13-diangeloyloxylongipinan-1-one (10), isolated from the roots of Stevia viscida, gave alcohols 27 or 28, respectively, which were subjected to molecular rearrangements with boron trifluoride etherate. Compound 27 afforded (3R,4R,5R,6S,9R,10S,11S)-11,13-oxyneomorelian-1-one (33) and (4S,5R,6S,8S,10R)-10,13-oxyneojiquilp-2-en-1-one (34), both possessing novel sesquiterpenoid skeletons. In turn, 28 provided (3R,4R,5S,6S,9R,11R)-13-hydroxymoreli-10(14)-en-1-one (32) and 33. Acetylation of 28 gave 29, thus allowing reduction of the C-1 carbonyl group to yield 30, which was rearranged to (1S,3R,4S,5S,6S,9R,10R,11R)-13-acetoxy-9,11-epoxyjiquilpane (31), while an attempt to mesylate 28 directly gave rearranged (3R,4R,5S,6S,9R,11R)-13-mesyloxymoreli-10(14)-en-1-one (35) through expulsion of the C-9 mesylate group by the antiperiplanar C-4−C-10 bond migration to C-4−C-9. In addition, treatment of 10 with boron trifluoride etherate generated (3R,4R,5S,6S,9R,11R)-13-angeloyloxymoreli-10(14)-en-1-one (36). The structures of 27−36 were elucidated by 1D and 2D NMR experiments and those of 27, 28, 33, 34, and 35 were confirmed by single-crystal X-ray diffraction analysis.

La hidrólisis parcial o total de la (3R,4S,5S,6S,9R,10R,11R)-9,13-diangeloiloxilongipinan-1-ona (10), aislada de las raíces de Stevia viscida, genera los alcoholes 27 ó 28, respectivamente, los cuales se sometieron a reordenamientos moleculares con eterato de trifluoruro de boro. El compuesto 27 proporcionó la (3R,4R,5R,6S,9R,10S,11S)-11,13-oxineomorelian-1-ona (33) y la (4S,5R,6S,8S,10R)-10,13-oxineojiquilp-2-en-1-ona (34), ambas poseyendo esqueletos sesquiterpenoides novedosos. A su vez, 28 proporcionó la (3R,4R,5S,6S,9R,11R)-13-hidroximoreli-10(14)-en-1-ona (32) y 33. La acetilación de 28 dio 29, permitiendo así la reducción del grupo carbonilo en C-1 para formar 30, que se reordenó a (1S,3R,4S,5S,6S,9R,10R,11R)-13-acetoxi-9,11-epoxijiquilpano (31), mientras que un intento de mesilar 28 condujo directamente a un reordenamiento generando la (3R,4R,5S,6S,9R,11R)-13-mesiloximoreli-10(14)-en-1-ona (35) a través de la expulsión del grupo mesilato de C-9 por la migración antiperiplanar del enlace C-4−C-10 hacia C-4−C-9. Además, el tratamiento de 10 con eterato de trifluoruro de boro generó la (3R,4R,5S,6S,9R,11R)-13-angeloiloximoreli-10(14)-en-1-ona (36). Las estructuras de 27−36 fueron elucidadas mediante experimentos de RMN en 1D y 2D, y las de 27, 28, 33, 34 y 35 fueron confirmadas por análisis de difracción de rayos X de monocristal.
Instituto de Investigaciones Químico Biológicas. Doctorado en Ciencias Químicas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6288; info:eu-repo/classification/cti/2; IIQB-D-2021-1494; Transposición; Wagner-Meerwein; Sesquiterpenoide